Sodium aluminum hydrogen tetra-hydrogen storage material as well as preparation method and application thereof

By using the method of smelting and fast melting quenching under an inert atmosphere in the preparation of sodium aluminum hydrogen storage materials, the problems of low raw material activity and slow hydrogen absorption and release kinetics in the preparation of sodium aluminum hydrogen storage materials are solved, and the effects of high purity, low hydrogen release temperature and high hydrogen release rate are achieved.

CN120208161APending Publication Date: 2025-06-27XIAN TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510383328.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

In the prior art, the preparation raw material activity of sodium-aluminum-hydrogen 4 composite hydrogen storage materials is low, the synthesis conditions are high, and the kinetics of hydrogen absorption and release are slow.

Method used

The aluminum element and metal catalyst were melted under an inert atmosphere to form an alloy ingot, and the aluminum alloy belt was obtained by performing rapid melting and quenching. Then, the sodium aluminum hydrogen tetrahydrogen storage material was ball milled with sodium hydride under a reduction atmosphere containing hydrogen to obtain a sodium aluminum hydrogen tetrahydrogen storage material.

Benefits of technology

The NaAlH4 purity and hydrogen release amount of sodium-aluminum hydrogen storage materials have been improved, the hydrogen release temperature and activation energy have been reduced, the hydrogen release rate has been significantly accelerated, and the process is simplified, environmentally friendly, and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120208161A_ABST
    Figure CN120208161A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogen storage material preparation, in particular to a Na-Al-H4 hydrogen storage material and a preparation method and application thereof. The invention provides a preparation method of a Na-Al-H4 hydrogen storage material, which comprises the following steps: in an inert atmosphere, smelting an aluminum elementary substance and a metal catalyst to obtain an aluminum alloy ingot, and then melting and rapidly quenching the aluminum alloy ingot to obtain an aluminum alloy strip; and carrying out ball milling and hydrogenation on the aluminum alloy belt and sodium hydride in a hydrogen-containing reducing atmosphere to obtain the Na-Al-H4 hydrogen storage material. An aluminum alloy ingot is obtained through smelting, then the alloy ingot is subjected to melting and rapid quenching to obtain an aluminum alloy belt, and the aluminum alloy belt and sodium hydride are subjected to ball-milling hydrogenation in the form of the aluminum alloy belt to obtain the Na-Al-H4 hydrogen storage material. The whole process adopts a solid-solid reaction preparation method, the raw materials are simple and easy to obtain, the use of an organic solvent is avoided in the process, the operation is simple, and the method is suitable for large-scale factory preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen storage material preparation, and particularly relates to a sodium aluminum hydride hydrogen storage material, a preparation method thereof, and an application thereof. Background Art

[0002] As one of the three key new energies in the 21st century, hydrogen energy shows significant potential as a future energy carrier. However, the main challenge currently faced in its large-scale application is the lack of safe, efficient, and economical hydrogen storage and transportation technologies. Solid-state hydrogen storage technology generates metal or coordination metal hydrides through physical adsorption or chemical reactions between hydrogen storage materials and hydrogen. Compared with other solid-state hydrogen storage materials, such as metal borohydrides, aluminum hydrides have the advantages of high hydrogen storage density, low hydrogen release temperature, high purity, and low cost. In addition, the good compatibility of aluminum hydrides with proton exchange membrane fuel cell technology makes them more advantageous in practical applications.

[0003] In 1997, Bogdanovic, Schwickardi, etc. creatively improved the hydrogen absorption and desorption rates of the NaAlH4 system by adding a Ti catalyst. Due to its high hydrogen release amount, low hydrogen release temperature, and excellent cycling performance, it has attracted extensive research by scholars ( Borislav, and Manfred Schwickardi. Ti-doped alkali metal aluminium hydrides as potential novel reversible hydrogen storage materials. Journal of alloys and compounds, 1997, 253: 1-9.). The mass hydrogen storage density of NaAlH4 is 7.5 wt%, which is one of the solid hydrogen storage materials with relatively high hydrogen storage density. The enthalpy change values of the first and second hydrogen release reactions are 37 and 47 kJ / mol respectively, showing good reversibility thermodynamically. In early industrial production and laboratory preparation of NaAlH4, the liquid phase method was generally used. In solvents such as THF or hexane, NaH and aluminium halide were synthesized under the condition of a catalyst. Although this method can make the reactants disperse evenly and the reaction process is easy to control, due to the use of easily decomposable organic solvents which are toxic, the organic solvents need to be removed from the product, resulting in high cost, and it is easy to introduce impurities (such as some anions), causing the obtained powder to have insufficient purity, many by-products, difficult separation and complex operation. In 2005, Bellosta et al. directly ball-milled a mixture of NaH, Al and TiCl3 at 50-70 °C and an initial hydrogen pressure of 83 bar, and Ti-doped NaAlH4 with a hydrogen absorption capacity of 3.96 wt% could be synthesized in one step, with relatively low required temperature and pressure, and excellent kinetic performance during synthesis (Von Colbe et al, One-step direct synthesis of a Ti-doped sodium alanate hydrogen storage material. Chemical communications, 2005, 37: 4732-4734.). However, the impurity anions introduced when adding the catalyst will react with Na +Combining to form stable sodium salts, it significantly reduces the effective hydrogen storage capacity of the system, decreases the product conversion rate and purity. Later, attempts were made to add other elemental metal powders as catalysts, such as Ti, Ce, Sc, etc. Compared with alloys such as TiF3, TiC, TiN, ScCl3, CeCl3, Ti - Al, CeAl, using elemental metals as catalysts avoids the formation of inert by - products, but the catalytic activity is significantly reduced. The solid - phase method greatly simplifies the synthesis steps of NaAlH4, is more efficient, can store hydrogen on a large scale, and is environmentally friendly without solvent removal, but the pressure required during ball milling is too high, which requires high - performance synthesis equipment, high energy consumption, and the catalyst has poor dispersibility, the reaction is incomplete, and there is a safety hazard of dust explosion for the raw material aluminum powder. Meanwhile, the activation energies of the first two hydrogen - releasing reactions of NaAlH4 are 118 - 128 and 120 - 159 kJ / mol respectively, with high kinetic energy barriers. The high reaction activation energy makes it difficult for NaAlH4 to reversibly absorb and release hydrogen under relatively mild conditions, seriously affecting the hydrogen absorption and release kinetics of the system.

[0004] Therefore, the current high - performance NaAlH4 preparation technology cannot meet the actual needs. Summary of the Invention

[0005] The present invention aims to overcome the problems of low activity of raw materials, high requirements for synthesis conditions, and slow hydrogen absorption and release kinetics of sodium aluminum hydride composite hydrogen storage materials in the prior art, and provides a sodium aluminum hydride hydrogen storage material, its preparation method and application to overcome the above - mentioned defects.

[0006] To achieve the above - mentioned purpose, the present invention provides the following technical solutions:

[0007] The present invention provides a preparation method of a sodium aluminum hydride hydrogen storage material, including:

[0008] S1. Under an inert atmosphere, aluminum and a metal catalyst are melted to obtain an aluminum alloy ingot, and then the aluminum alloy ingot is subjected to melt spinning to obtain an aluminum alloy ribbon;

[0009] S2. Under a reducing atmosphere containing hydrogen, the aluminum alloy ribbon and sodium hydride are ball - milled and hydrogenated to obtain a sodium aluminum hydride hydrogen storage material.

[0010] In the present invention, aluminum and other metals are first melted to obtain an alloy ingot. In this process, the metal catalyst is integrated with aluminum, and the in - situ formed intermetallic compound catalyst Al n M (M is the metal in the metal catalyst, the same below) has the functions of catalysis and refining the matrix grain.

[0011] During the melt-spinning quenching process, the metal catalyst is uniformly dispersed in the alloy strip. During the quenching process, after the rapid heating ends, the alloy immediately contacts the copper roller. Therefore, the high cooling rate during the cooling process significantly shortens the atomic diffusion time and reduces the segregation of the metal catalyst in the alloy. In addition, the rapid cooling process can promote the formation of Al n M crystal nuclei and inhibit grain growth, thereby controlling the size of the alloy at the nanoscale. Meanwhile, the formed intermetallic compound Al n M serves as a heterogeneous nucleation center, and its dispersed distribution provides a large number of nucleation sites, reduces the energy barrier required for Al nucleation, and refines the Al grains.

[0012] High-energy ball milling introduces high-density lattice defects (such as dislocations and vacancies), refines the particles, and dynamically reconstructs the surface to generate a nano-intermetallic compound catalytic interface, resulting in a sodium aluminum hydride hydrogen storage material with stable performance and structure.

[0013] The finally obtained sodium aluminum hydride hydrogen storage material has a high purity of NaAlH4 and few other phase impurities; it has a lower hydrogen release temperature. The in-situ generated catalyst reduces the hydrogen release activation energy of the whole system, accelerates the hydrogen release rate, and the hydrogen release amount ≥ 4.5 wt%.

[0014] Preferably, in the S1, the metal catalyst is a metal element or an intermediate alloy.

[0015] Preferably, the metal element is Ti, Ce, Sc, Zr, Co, Ni, La or Sm.

[0016] Preferably, the intermediate alloy is AlNb 10 、AlMo5 or AlV 10 .

[0017] Preferably, the inert gas includes argon.

[0018] Preferably, the aluminum element is aluminum element particles.

[0019] Compared with aluminum powder, the aluminum particles have less surface oxide layer and no safety hazard of dust explosion, which is a better choice.

[0020] Preferably, in the S1, the dosage of the metal catalyst is 6-10 wt% of the aluminum element.

[0021] Preferably, in the S1, the metal catalyst is in particulate form.

[0022] Preferably, in the S1, the chamber pressure during melting ≤ -0.05 MPa.

[0023] Preferably, during melting, first evacuate the vacuum and then introduce an inert gas.

[0024] Preferably, evacuate the vacuum to a vacuum degree ≤ 0.003 Pa.

[0025] Preferably, an inert gas is introduced until the chamber pressure is -0.05 to -0.1 MPa.

[0026] Preferably, after the aluminum and the metal catalyst are melted, they are further melted under stirring to obtain an aluminum alloy ingot.

[0027] Preferably, cooling to the solid state after melting is defined as one-time melting, and the number of melting times is at least 5 times.

[0028] Preferably, the melting equipment is a vacuum arc melting furnace.

[0029] Preferably, in the step S1, during the melt spinning quenching, the vacuum is first evacuated and then the inert gas is introduced.

[0030] Preferably, the vacuum is evacuated to a vacuum degree ≤ 0.003 Pa.

[0031] Preferably, the inert gas is introduced until the internal pressure is -0.05 to -0.1 MPa.

[0032] Preferably, the injection pressure of the inert gas is 0.05 to 0.15 MPa.

[0033] Preferably, the rotation speed during the melt spinning quenching is 1000 to 3000 rpm.

[0034] Preferably, the heating power during the melt spinning quenching is 1 to 2 Kw and is maintained for 5 to 20 s.

[0035] Preferably, the equipment for melt spinning quenching is a high-vacuum levitation melting and strip casting furnace.

[0036] Preferably, in the step S2, the molar ratio of aluminum to sodium hydride in the aluminum alloy strip is 1:1.

[0037] Preferably, the ball milling conditions are: the ball-to-material ratio is 100 to 150:1, the rotation speed is 300 to 500 rpm / min, and the time is 20 to 40 h.

[0038] The longer the ball milling time, the more beneficial it is to the formation of the effective substance of NaAlH4. However, considering that the conversion rate improvement is relatively limited after excessively prolonging the ball milling time. From the perspective of saving time, the ball milling time of 20 to 40 h can already achieve a better conversion rate. However, it should be considered that the ball milling time setting above 40 h is substantially the same as the solution of the present invention and is still within the protection scope of the present invention.

[0039] Preferably, the hydrogen content in the reducing atmosphere containing hydrogen is ≥ 99.0%.

[0040] Preferably, the hydrogen pressure of the reducing atmosphere containing hydrogen is 20 to 60 bar.

[0041] The present invention provides a sodium aluminum tetrahydride hydrogen storage material, which comprises NaAlH4 and Na3AlH6; based on the weight of the sodium aluminum tetrahydride hydrogen storage material, the content of NaAlH4 is above 90 wt%.

[0042] The sodium aluminum tetrahydride hydrogen storage material synthesized by the present invention has a lower hydrogen release temperature, and the in-situ generated catalyst reduces the hydrogen release activation energy of the system, which is mainly manifested in the synthesized nanoscale Al n The high specific surface area and porosity of M provide a large number of hydrogen dissociation sites, promoting electron transfer and hydrogen dissociation; M enters the interior of the NaAlH4 lattice to replace Na / Al atoms, changing the electronic structure of NaAlH4 and promoting H - to lose electrons, making the Al-H bond unstable and broken, and accelerating the hydrogen release process of NaAlH4. At the same time, the in-situ generated active Al n M is dispersed on the surface of NaAlH4, accelerating the dissociation and adsorption of H, and providing a nucleation core for the precipitation of Al and NaH.

[0043] In addition, the sodium aluminum tetrahydride hydrogen storage material has good cycle stability, which stems from the multi-scale structure synergistic effect: melt spinning and rapid cooling form nanocrystalline or amorphous Al n M, the atomic-level uniform distribution inhibits component segregation, and the short-range ordered defects of the amorphous phase construct active sites. At the same time, high-energy ball milling introduces high-density lattice defects (such as dislocations and vacancies), refines particles and dynamically reconstructs the surface to generate a nanoscale intermetallic compound catalytic interface. Al n M has a stable structure and exists stably in the reaction, jointly promoting the cycle stability of the product NaAlH4.

[0044] The present invention provides a hydrogen storage material, which comprises the above-mentioned sodium aluminum tetrahydride hydrogen storage material.

[0045] The present invention provides a hydrogen storage device, which uses the above-mentioned sodium aluminum tetrahydride hydrogen storage material.

[0046] Based on the hydrogen release characteristics and cycle stability of the above-mentioned sodium aluminum tetrahydride hydrogen storage material, it can be used as a component in hydrogen storage materials or as a raw material for hydrogen storage devices.

[0047] Therefore, the present invention has the following beneficial effects:

[0048] (1) In the present invention, an aluminum alloy ingot is obtained by melting, and then the alloy ingot is melt-spun and rapidly quenched to obtain an aluminum alloy strip. The sodium aluminum tetrahydride hydrogen storage material is obtained by ball-milling the aluminum alloy strip with sodium hydride. The whole process adopts a solid-solid reaction preparation method, and the raw materials are simple and easy to obtain. The use of organic solvents is avoided during the process, and the operation is simple, which is suitable for large-scale preparation in factories.

[0049] (2) The nano-scale aluminum alloy strip obtained by smelting and rapid quenching in the present invention plays a key role in the subsequent material synthesis. On the one hand, the Al n M acts as a surface active site, reducing the hydrogen dissociation energy barrier; on the other hand, Al generated in situ during the melt quenching process n M enters into the Al lattice and acts as a heterogeneous nucleation center to increase the nucleation rate, refine the Al grains, and shorten the diffusion distance of hydrogen atoms.

[0050] (3) The present invention uses aluminum particles and metal single substance / intermediate alloy particles for smelting, which can avoid the problem of aluminum powder explosion; in addition, the sodium aluminum hydrogen tetrahydrogen storage material with ideal performance cannot be obtained by directly smelting the metal single substance / intermediate alloy in powder form with aluminum particles.

[0051] (4) The NaAlH4 in the sodium aluminum hydride tetrahydrogen storage material obtained by the present invention has high purity and contains few impurities of other phases; it has a lower dehydrogenation temperature, and the catalyst generated in situ reduces the dehydrogenation activation energy of the entire system, so that the dehydrogenation rate is accelerated, and the dehydrogenation amount is ≥4.5wt%. Based on the above properties, the obtained sodium aluminum hydride tetrahydrogen storage material has a wide range of application prospects, and the present invention provides a new idea and a new basic material for other hydrogen storage research. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 XRD patterns of alloy strips after arc melting and melt quenching of titanium-doped aluminum particles and undoped aluminum particles prepared in Example 1 and Comparative Example 1 of the present invention, wherein Al-4Ti, Al-6Ti, Al-8Ti, and Al-10Ti are aluminum alloy strips of Example 1, and Al is the aluminum strip of Comparative Example 1;

[0053] Figure 2 The SEM images of the alloy strips after arc melting and melt quenching of titanium-doped aluminum particles and undoped aluminum particles prepared in Example 1 of the present invention and Comparative Example 1, wherein a to e are the copper roller contact surfaces of the Al-Ti alloy strips in different proportions, and f to j are the copper roller non-contact surfaces of the Al-Ti alloy strips in different proportions;

[0054] Figure 3 The SEM image and the corresponding EDS spectrum of the Al-6Ti alloy strip in Example 1 of the present invention, wherein a is the SEM image, b is the EDS image of Al, and c is the EDS image of Ti;

[0055] Figure 4 TEM images and corresponding EDS spectra in Example 1 of the present invention, wherein a is a TEM image, b is an EDS image of Al, and c is an EDS image of Ti;

[0056] Figure 5 is a metallographic diagram of the Al-6Ti alloy strip in Example 1 of the present invention;

[0057] Figure 6 Metallographic diagram of the Al-6Ti alloy ingot of Comparative Example 2 of the present invention;

[0058] Figure 7 XRD patterns of the sodium aluminum hydride tetrahydrate hydrogen storage materials prepared in Example 1 and Comparative Example 1 of the present invention;

[0059] Figure 8 Hydrogen desorption curves with temperature of the sodium aluminum hydride tetrahydrate hydrogen storage materials prepared in Example 1 and Comparative Example 1 of the present invention;

[0060] Figure 9 Isothermal hydrogen desorption curves of the Al-6Ti alloy strip in Example 1 and the sodium aluminum hydride tetrahydrate hydrogen storage material prepared in Comparative Example 1 of the present invention;

[0061] Figure 10 Hydrogen desorption curves with temperature of the sodium aluminum hydride tetrahydrate hydrogen storage materials prepared in Example 1 (Al-6Ti alloy strip) and Comparative Example 2 (Al-6Ti as-cast) of the present invention;

[0062] Figure 11 Hydrogen desorption curves with temperature of the sodium aluminum hydride tetrahydrate hydrogen storage materials prepared in Comparative Example 3 and Comparative Example 4 of the present invention;

[0063] Figure 12 Hydrogen desorption curves with temperature of the sodium aluminum hydride tetrahydrate hydrogen storage material prepared from the Al-6Ti alloy strip in Example 1 of the present invention under different numbers of cycles;

[0064] Figure 13 XRD patterns of the sodium aluminum hydride tetrahydrate hydrogen storage material prepared from the Al-6Ti alloy strip in Example 1 of the present invention and its 1st, 2nd and 10th cycles, bm is the 1st time, abs 2 is the 2nd time, abs 10 is the 10th time;

[0065] Figure 14 XPS Ti 2p fine spectra of the sodium aluminum hydride tetrahydrate hydrogen storage material prepared from the Al-6Ti alloy strip in Example 1 of the present invention and its 1st, 2nd and 10th cycles, bm is the 1st time, Reh 01 is the 2nd time, Reh 10 is the 10th time;

[0066] Figure 15 XRD pattern of the sodium aluminum hydride tetrahydrate hydrogen storage material prepared in Example 2 of the present invention;

[0067] Figure 16 Hydrogen desorption curve with temperature of the sodium aluminum hydride tetrahydrate hydrogen storage material prepared in Example 2 of the present invention;

[0068] Figure 17 XRD pattern of the sodium aluminum hydride tetrahydrate hydrogen storage material prepared in Example 3 of the present invention;

[0069] Figure 18The hydrogen desorption curve with temperature of the sodium aluminum hydride storage hydrogen material prepared in Example 3 of the present invention. Detailed implementation manners

[0070] The present invention will be further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are usually only a part of the embodiments of the present invention, rather than all of the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the scope of protection of the present invention.

[0071]

Embodiment

[0072] Embodiment 1 Different ratios of Ti / Al

[0073] The metal catalyst precursor selected in this embodiment is Ti particles, and the sodium aluminum hydride storage hydrogen materials prepared from Al alloy strips with different Ti contents are explored, where the mass fraction of Ti in the alloy is x (x = 4, 6, 8, 10 wt%).

[0074] Step 1: Arc melting and mixing. Weigh aluminum particles and titanium particles according to the ratio in Table 1, put them into a vacuum arc melting furnace, close the furnace door and evacuate to 0.003 Pa, fill the furnace with argon gas to make the furnace pressure reach -0.05 MPa, turn on the arc gun switch, and make it melt by using the pre-placed titanium grains in the furnace to generate an arc. After cooling with no obvious color change, melt the prepared aluminum-titanium particles, increase the current to make it melt and then turn on the magnetic stirring to further melt, and then cool to the solid state. Flip and repeat the above operations 5 times to obtain an aluminum-titanium alloy ingot.

[0075] Table 1 Dosage table

[0076] x / wt% Mass of Al (g) Mass of Ti (g) Mass of Al-xTi belt (g) Mass of NaH (g) 0 35 / 0.529 0.471 4 33.6 1.4 0.540 0.460 6 32.9 2.1 0.545 0.455 8 32.2 2.8 0.550 0.450 10 31.5 3.5 0.555 0.445

[0077] Step 2: Melt spinning. Take 5 - 8 g of the above aluminum-titanium alloy ingot and put it into a quartz crucible installed in a high-vacuum levitation melting and spinning furnace. Evacuate to a vacuum degree of 0.003 Pa and then fill it with argon gas to make the chamber pressure reach -0.05 MPa. Adjust the argon gas casting pressure to 0.1 MPa, set the copper roller speed to 2000 rpm, and then adjust the heating power to 1.5 - 2 Kw. After maintaining for 10 s, perform casting to obtain an aluminum-titanium alloy strip (Al-xTi belt, x = 4, 6, 8, 10).

[0078] Step 3: Load samples with different contents of sodium hydride and aluminum in the above aluminum-titanium alloy belt in a molar ratio of 1:1 into a ball milling jar, with a ball-to-material ratio of 100:1. The grinding balls are made of stainless steel. Place the ball milling jar in an argon glove box and seal it. Take out the ball milling jar and evacuate it, then fill it with 50 bar of hydrogen and place it on a planetary ball mill for ball milling. Ball milling parameters: Run forward and backward alternately, with a rotation speed of 500 rpm / min, rotate for 12 minutes, stop for 6 minutes. After ball milling for 12 hours, remove the ball milling jar, scrape the material to make it loose and refill it with 50 bar of hydrogen, and use the same ball milling parameters to ball mill for another 12 hours to obtain the prepared sodium-aluminum-hydrogen quaternary hydrogen storage material, denoted as NaH / Al-xTi belt-HBM 24h (x = 4, 6, 8, 10).

[0079] Example 2 Different ratios of Ce / Al

[0080] The metal catalyst precursor selected in this example is Ce particles. The sodium-aluminum-hydrogen quaternary hydrogen storage materials prepared from Al alloy belts with different Ce contents are explored, where the mass fraction of Ce in the alloy is x (x = 4, 6, 8, 10 wt%).

[0081] Step 1: Arc melting and mixing. Weigh aluminum particles and cerium particles according to the ratio in Table 2, put them into a vacuum arc melting furnace, close the furnace door and evacuate to 0.003 Pa, fill the furnace with argon atmosphere to make the furnace pressure reach -0.05 MPa, turn on the arc gun switch, and make it melt by igniting with the pre-placed cerium grains in the furnace. After cooling with no obvious color change, melt the prepared aluminum-cerium particles, increase the current to make it melt and then turn on the magnetic stirring for further melting, and then cool to solid state. Flip and repeat the above operations 5 times to obtain an aluminum-cerium alloy ingot.

[0082] Table 2 Dosage table

[0083] x / wt% Mass of Al (g) Mass of Ce (g) Mass of Al-xCe belt (g) Mass of NaH (g) 4 33.6 1.4 0.540 0.460 6 32.9 2.1 0.545 0.455 8 32.2 2.8 0.550 0.450 10 31.5 3.5 0.555 0.445

[0084] Step 2: Melt spinning. Take 5 - 8 g of the above aluminum-cerium alloy ingot and put it into a quartz crucible installed in a high-vacuum levitation melting and spinning furnace. Evacuate to a vacuum degree of 0.003 Pa and then fill it with argon atmosphere to make the chamber pressure reach -0.05 MPa. Adjust the argon spray casting pressure to 0.1 MPa, set the copper roller rotation speed to 2000 rpm, then adjust the heating power to 1.5 - 2 Kw, and after maintaining for 10 s, spray cast to obtain an aluminum-cerium alloy belt (Al-xCe belt, x = 4, 6, 8, 10).

[0085] Step 3: Samples with different contents of sodium hydride and aluminum in the above aluminum-cerium alloy belt with a molar ratio of 1:1 were loaded into a ball milling jar, with a ball-to-material ratio of 100:1. The grinding balls were stainless steel balls. The ball milling jar was placed in an argon glove box and sealed. The ball milling jar was taken out and evacuated, and then filled with 50 bar of hydrogen and placed on a planetary ball mill for ball milling. Ball milling parameters: running alternately forward and backward, rotation speed 500 rpm / min, rotating for 12 min and stopping for 6 min. After ball milling for 12 h, the ball milling jar was removed, the material was scraped to make it loose and then filled with 50 bar of hydrogen again, and ball milled for another 12 h using the same ball milling parameters. This was repeated twice for a total of 36 h of ball milling to obtain the prepared sodium-aluminum-hydrogen quaternary composite hydrogen storage material, denoted as NaH / Al-xCe belt-HBM 36h (x = 4, 6, 8, 10).

[0086] Example 3 Sc / Al

[0087] The metal catalyst precursor selected in this example is Sc particles.

[0088] Step 1: Arc melting and mixing. Weigh 32.2 g of aluminum particles and 2.8 g of scandium particles (Sc content 8 wt%). Put them into a vacuum arc melting furnace, close the furnace door and evacuate to a vacuum degree of 0.003 Pa. Fill the furnace with argon atmosphere to make the furnace pressure reach -0.05 MPa. Turn on the arc gun switch, and use the pre-placed scandium particles in the furnace to initiate the arc to make it melt. After cooling with no obvious color change, melt the prepared aluminum-scandium particles, increase the current to make it melt and then turn on the magnetic stirrer to further melt, and then cool to solid state. Flip and repeat the above operations 5 times to obtain an aluminum-scandium alloy ingot.

[0089] Step 2: Melt spinning. Take 5 - 8 g of the above aluminum-scandium alloy ingot and put it into a quartz crucible installed in a high-vacuum arc melting and spinning furnace. Evacuate to a vacuum degree of 0.003 Pa and then fill with argon atmosphere to make the chamber pressure reach -0.05 MPa. Adjust the argon spray casting pressure to 0.1 MPa, set the copper roller rotation speed to 2000 rpm, then heat power to 1.5 - 2 Kw, and spray cast after maintaining for 10 s to obtain an aluminum-scandium alloy belt (Al-8Sc belt).

[0090] Step 3: Samples with different contents of sodium hydride and aluminum in the above aluminum-scandium alloy belt in a molar ratio of 1:1 were loaded into a ball milling jar with a ball-to-material ratio of 100:1. The grinding balls were stainless steel balls. The ball milling jar was sealed in an argon glove box, taken out and evacuated, filled with 50 bar of hydrogen, and then ball milled on a planetary ball mill. Ball milling parameters: running alternately forward and backward, rotation speed 500 rpm / min, rotating for 12 min and stopping for 6 min. After ball milling for 12 h, the ball milling jar was removed, the material was scraped to make it loose and then filled with 50 bar of hydrogen again, and ball milled for another 12 h using the same ball milling parameters. This was repeated twice for a total of 36 h of ball milling to obtain the prepared sodium-aluminum-hydrogen quaternary composite hydrogen storage material, denoted as NaH / Al-8Sc belt-HBM 36h.

[0091] Comparative Example 1: No catalyst was added.

[0092] This comparative example had the same operating steps as Example 1. 35.0 g of aluminum particles (Ti content 0 wt%) in Table 1 were selected, and the obtained product was denoted as NaH / Al belt HBM 24h.

[0093] Comparative Example 2: No melt spinning was carried out.

[0094] This comparative example had the same operating steps as Example 1, except that: Step 2 was cancelled; the alloy ingot obtained in Step 1 was denoted as Al-6Ti cast, and the product was denoted as NaH / Al-6Ti cast HBM 24h.

[0095] Comparative Example 3

[0096] This comparative example had the same operating steps as Example 1, except that: 0.016 g of arc-melted and rapidly quenched Al3Ti alloy belt and pure Al belt were used to replace the catalyst-integrated Al-6Ti alloy belt as reactants. The amount of Al belt used was 0.529 g, and the amount of NaH used was 0.455 g. The product was denoted as NaH / Al-6Al3Ti belt HBM 24h.

[0097] Comparative Example 4

[0098] This comparative example had the same operating Step 3 as Example 1, but without the first two steps of melting and rapid quenching treatment. 0.016 g of titanium powder and pure Al belt were directly used to replace the catalyst-integrated Al-6Ti alloy belt as reactants. The amount of pure Al belt used was 0.529 g, and the amount of NaH used was 0.455 g. The product was denoted as NaH / Al-6Ti powder HBM 24h.

[0099]

Performance Test

[0100] 1. Apparent Structure

[0101] The alloy tapes under various ratio conditions obtained in Example 1 and Comparative Example 1 were subjected to XRD analysis, and the results are as Figure 1 shown. It can be observed that after adding Ti, the diffraction peak intensity of Al in the alloy is lower than that of pure Al, and with the increase of the Ti addition amount, the diffraction peak of the second phase Al3Ti appears. When the Ti addition amount is 4 wt%, no obvious Al3Ti phase is observed. After the Ti addition amount is increased to 6 wt%, obvious Al3Ti diffraction peaks are observed in the Al-Ti alloy. By carefully comparing the diffraction peaks of the Al3Ti phase, the characteristic diffraction peaks of the (111) and (200) crystal planes of the metastable phase structure (space group Pm3m) of Al3Ti are detected in Al-6Ti, corresponding to 2θ angles of 39.256° and 45.64°; in addition to retaining the metastable phase diffraction peaks in the Al-8Ti and Al-10Ti samples, the diffraction peaks of the (103), (004) and (200) crystal planes of the stable phase (space group I4 / mmm) also appear at 39.080°, 41.927° and 47.194°. It should be noted that the Al peak intensity in Al-6Ti is the lowest, mainly because compared with the stable phase of Al3Ti, the lattice constant of its metastable phase is close to that of α-Al, the interface mismatch degree is lower, and the crystal structure types are the same. The two have a high crystallographic match, significantly reducing the nucleation interface energy and providing an ideal heterogeneous nucleation center for α-Al.

[0102] Figure 2 Morphology characteristics of the copper roller contact surfaces ( Figure 2 a-e) and non-contact surfaces ( Figure 2 f-j) of Al-Ti alloy tapes with different ratios, where the grain sizes of the copper roller contact surfaces ( Figure 2 b-e) and non-contact surfaces ( Figure 2 g-j) of Al-xTi are smaller than those of pure Al ( Figure 2 a and Figure 2 f), and when the Ti content is above 6 wt%, obvious porous characteristics are shown ( Figure 2 c-e, Figure 2 h-j), and among the alloy tapes with different Ti contents, the grain size of the Al-6Ti sample is the smallest (400-800 nm) and relatively uniform. This further confirms the refining effect of in-situ generated Al3Ti as a heterogeneous nucleation center on Al grains during the rapid cooling process.

[0103] Figure 3 Microscopic morphology of the Al-6Ti belt. It is observed that the overall material shows two morphologies, with a spherical particle porous area. According to the EDX element distribution, the Ti element is evenly distributed in both areas. It is proved that after arc melting and melt spinning, Ti substances are evenly dispersed on the aluminum matrix.

[0104] Figure 4Transmission image of the Al-6Ti belt. EDX energy spectrum shows two different substrates. The darker area is the Al matrix, and the rectangular sheet-like area in the bright area shows a columnar Ti element distribution region, which is relatively evenly dispersed, with a length of about 400 - 800 nm and a width reduced to 100 - 300 nm. Combining Figure 1 with the XRD analysis in

[0105] Figure 5 , 6 are the metallographic diagrams of the Al-6Ti belt and the Al-6Ti cast respectively. The figure shows that the Al-6Ti cast sample slowly cools after arc melting and solidifies into thick columnar crystals of Al3Ti, which are of different sizes and unevenly distributed, with a size of about 2 - 6 μm; while for the Al-6Ti belt sample, rapid cooling ensures a high degree of supercooling, inhibits the growth of columnar crystals, and promotes the formation of equiaxed crystals, forming fine equiaxed solidification structures in the ingot, with a grain size of 400 - 800 nm. The fine equiaxed crystal structure can make the second phase evenly distributed, with a low crystal misfit degree between it and α-Al, located at the center of the α-Al grains, and spontaneously promotes the nucleation of α-Al grains during the cooling process. Therefore, it can significantly increase the number of nucleation, inhibit grain growth, and improve the grain refinement effect.

[0106] Figure 7XRD patterns of sodium alanate hydrogen storage materials prepared with Al ribbon and Al-Ti alloy ribbon as aluminum sources. After the pure Al ribbon without Ti catalyst was hydrogenated with NaH, only a very small amount of Na3AlH6 was generated, and most of the products were still Al and NaH. This is because in the absence of a catalyst, due to the high kinetic energy barrier, the hydrogenation reaction between Al and NaH is difficult. The addition of Ti catalyst significantly improved the hydrogenation reaction degree of Al alloy and NaH. When the Ti addition amount was 4 wt%, obvious diffraction peaks of Na3AlH6 and NaAlH4 could be observed, but there was still a large amount of unreacted Al and NaH. When the Ti addition amounts were 6 wt% and 8 wt%, NaAlH4 became the main substance in the products, and the amounts of residual Al and NaH were also greatly reduced. When the Ti addition amount increased to 10 wt%, the peak intensity of NaAlH4 decreased, and the peak intensity of Na3AlH6 increased. This change is mainly related to the content and phase structure of Al3Ti generated during the process. When the Ti addition amount was 4 wt%, less Al3Ti was generated, which promoted the conversion of NaH to NaAlH4 to a certain extent. When the Ti addition amount was 6 wt%, the low interface energy between the metastable Al3Ti and Al generated increased the heterogeneous nucleation efficiency greatly, refined the aluminum grains, and strengthened the solid-phase reaction kinetics between the two phases of Al and NaH, making the synthesis efficiency of NaAlH4 reach the peak. When the Ti addition amount was 8 wt%, the amount of thermodynamically stable Al3Ti phase in the system increased, and this structural evolution led to a weakening of its heterogeneous nucleation effect and a decrease in the aluminum grain refinement effect, resulting in a downward trend in the conversion efficiency. When the Ti addition amount was 10 wt%, the proportion of the stable Al3Ti phase further increased, the aluminum grain size could not be effectively reduced, and the conversion process was hindered to a large extent, resulting in a decrease in the reaction conversion degree. This non-linear relationship between phase structure evolution and catalytic performance reveals the important mechanism of the existence of an optimal threshold for titanium doping amount.

[0107] 2. Hydrogen release performance

[0108] Based on the characterization of the above apparent structure, it was found that the alloy ribbon with the ratio of Al-6Ti in Example 1 showed the best structural characteristics. Therefore, the hydrogen release performance was tested for it in this part.

[0109] Figure 8Non-isothermal dehydrogenation results of sodium alanate hydrogen storage materials prepared with Al ribbon and Al-Ti alloy ribbon as aluminum sources. Compared with the case without adding a catalyst, the aluminum hydride prepared with Al-Ti alloy ribbon as the aluminum source shows significantly increased dehydrogenation capacity and decreased dehydrogenation temperature. After ball milling for 24 h, the product of the hydrogenation reaction between pure Al ribbon and NaH starts dehydrogenating at 169.5 °C, and the dehydrogenation capacity up to 250 °C is only 0.83 wt%. For the NaH / Al-4Ti belt-HBM 24 h sample, the initial dehydrogenation temperature is 123.9 °C, a decrease of 45.6 °C. The second-step dehydrogenation temperature is 153.7 °C, and dehydrogenation ends at 218.8 °C. Up to 250 °C, the dehydrogenation capacity increases to 2.46 wt%. For the NaH / Al-6Ti belt-HBM 24 h sample, the initial dehydrogenation temperature is 103.8 °C, the second step starts dehydrogenating at 138.2 °C, and dehydrogenation ends at 189.2 °C. Up to 250 °C, the dehydrogenation capacity reaches 4.74 wt% of hydrogen. For the NaH / Al-8Ti belt-HBM 24 h sample, the initial dehydrogenation temperature decreases to 107.5 °C, and the second step starts dehydrogenating at 140.5 °C, and dehydrogenation ends at 187.7 °C. Up to 250 °C, 4.66 wt% of hydrogen can be released. For the NaH / Al-10Ti belt-HBM 24 h sample, the initial dehydrogenation temperature further decreases to 103.7 °C, the second step starts dehydrogenating at 140.5 °C, and dehydrogenation ends at 184.5 °C. Up to 250 °C, 4.22 wt% of hydrogen can be released. Among them, the NaH / Al-6Ti belt-HBM 24 h sample shows the best hydrogen storage and release performance.

[0110] Figure 9Isothermal hydrogen desorption curves of the NaH / Al-6Ti belt-HBM 24h sample at 120 °C, 135 °C and 160 °C and the NaH / Al belt-HBM 24h at 160 °C. As shown in the figure, the NaH / Al-6Ti belt-HBM 24h sample rapidly releases 4.74 wt% of hydrogen within 50 min at 160 °C, while the NaH / Al belt-HBM 24h sample only releases 0.57 wt% of hydrogen even after holding for 150 min at 160 °C. When the operating temperature is reduced to 120 °C, the NaH / Al-6Ti belt-HBM 24h sample also releases approximately 3.6 wt% of hydrogen within 140 min, indicating a significant improvement in desorption kinetics. This significant improvement is mainly attributed to the in-situ doping of Ti, which forms uniformly dispersed metastable Al3Ti in the Al matrix. Due to its high specific surface area and porosity, it provides a large number of hydrogen dissociation sites, promotes electron transfer and hydrogen dissociation, and the metastable phase of Al3Ti provides heterogeneous nucleation centers for Al, greatly reducing the grain size of aluminum, significantly shortening the diffusion distance of hydrogen atoms, constructing a high-speed grain boundary channel, which is conducive to enhancing the diffusion of hydrogen in the matrix and significantly improving the kinetic performance.

[0111] Figure 10 Non-isothermal hydrogen desorption diagrams of Al-6Ti belt and as-cast Al-6Ti powder (Comparative Example 2) as aluminum sources for the synthesis products. Only a small amount of NaAlH4 was synthesized using as-cast Al-6Ti, and most of the products were intermediate phases Na3AlH6, Al, and a very small amount of Al3Ti. The product starts to desorb hydrogen at 130 °C and ends the two-step hydrogen desorption at 224 °C, with a hydrogen desorption amount of only 2.09 wt%. This shows that the catalyst distribution in the arc-melted sample is extremely uneven, resulting in a decrease in catalytic performance. For the sample after melt spinning, the catalyst greatly promotes the hydrogen storage melting and hydrogen desorption temperature of the system.

[0112] Figure 11 The performance of directly synthesizing NaAlH4 using Ti powder (Comparative Example 4) and Al3Ti alloy belt (Comparative Example 3) as catalysts is not ideal. The non-isothermal hydrogen desorption results clearly show that due to the catalytic effect of Ti, the NaH / Al-6Al3Tibelt HBM 24h and NaH / Al-6Ti powder HBM 24h start to desorb hydrogen at around 160 °C, which is lower than the desorption temperature of catalyst-free NaH / Al belt-H. When heated to 218 °C, only 2.35 wt% of hydrogen is released. For the preparation of alloy ingots by melting titanium grains and aluminum grains, the specific surface area of Ti powder is large and it is easy to oxidize (the oxidation degree during storage is significantly higher than that of titanium grains), particle agglomeration leads to uneven dispersion, and due to the electronic structure limitation of zero-valent titanium, its catalytic activity is lower than that of high-valent titanium. When adding an Al3Ti alloy belt as a catalyst, there is a problem of catalyst dispersion, resulting in no obvious improvement in performance.

[0113] Figure 12 For the cyclic stability of the NaH / Al-6Ti belt HBM for 24 h, the initial hydrogen desorption temperature decreased to 90.4 °C and the hydrogen desorption amount decreased to 4.02 wt% during the second cycle. From the third cycle, the cycle became stable and tended to balance. Further XRD analysis showed that, as Figure 13 , after 10 cycles, the main substance in the hydrogenated sample was still NaAlH4. At the same time, the peak of Na3AlH6 was significantly enhanced at 2θ = 32.85°. The presence of this compound indicated incomplete hydrogenation during cycling, which was the reason for the decrease in dehydrogenation ability. The steady-state Al3Ti phase could still be seen in the XRD pattern of the sample after 10 cycles, which was one of the important reasons for the significant improvement in the cyclic stability of the NaH / Al-6Ti belt-HBM 24h sample.

[0114] Figure 14 For the NaH / Al-6Ti belt HBM 24h sample, Ti 2p peaks were observed at 450.57 eV, 456.06 eV, 453.43 eV, and 457.74 eV, corresponding to the 2p3 / 2-2p1 / 2 spin-orbit doublets of Al-Ti and Ti 0 , and the signal intensity of metallic Ti exceeded that of the Ti-Al phase. This indicated that part of the Al was removed from the Ti-Al phase and might combine with NaH to form NaAlH4, resulting in an increase in metallic Ti. During the second cycle, the Ti-Al peak increased and the Ti 0 peak decreased significantly, indicating the transformation of metallic Ti to Ti-Al. Ti reacted with the Al generated by the decomposition of NaAlH4 during heating and hydrogen absorption. This result was consistent with the significant decrease in the hydrogen desorption amount during the second cycle. After experiencing 2 hydrogen absorption and desorption cycles, the XPS spectrum no longer changed further, and at this time, the signal intensities of metallic Ti and Ti-Al were basically the same. Therefore, the increase in the Ti-Al phase with higher catalytic activity was the main reason for the activation phenomenon.

[0115] Figure 15 The XRD pattern of Example 2 is shown. It can be found from the figure that the optimal addition amount of Ce is 6 wt%. At this time, the peak intensity of the synthesized NaAlH4 is the highest, and a large number of Al4Ce peaks exist in the system. The in-situ alloyed nano-Al4Ce has strong activity, which promotes the synthesis of NaAlH4.

[0116] Figure 16 The hydrogen desorption diagram as a function of temperature of Example 2 is shown. Using the Al-6Ce belt as the aluminum source, the hydrogen desorption temperature of the product is 109.6 °C, the two-step hydrogen desorption temperature is 197.1 °C, and the hydrogen desorption amount is 4.88 wt%, which is the largest, consistent with the XRD results.

[0117] Figure 17 XRD pattern of Example 3 shows that a large amount of NaAlH4 was successfully synthesized, with a small amount of Na3AlH6 present. At the same time, the synthesized product contains the intermetallic compound Al3Sc as a catalyst, which promoted the reaction.

[0118] Figure 18 Hydrogen desorption curve with temperature of Example 3: Using an Al-8Sc alloy strip as the aluminum source, the hydrogen desorption temperature of the product is 115 °C, the two-step hydrogen desorption temperature is 174.4 °C, and the hydrogen desorption capacity is 4.5 wt%, showing excellent hydrogen storage performance.

Claims

1. A method for preparing a sodium aluminum hydrogen tetrahydrogen storage material, characterized in that: include: S1. Under an inert atmosphere, aluminum and a metal catalyst are smelted to obtain an aluminum alloy ingot, and then the aluminum alloy ingot is melted and rapidly quenched to obtain an aluminum alloy strip; S2. In a reducing atmosphere containing hydrogen, the aluminum alloy strip and sodium hydride are ball-milled and hydrogenated to obtain sodium aluminum hydride tetrahydrogen storage material.

2. The preparation method according to claim 1, characterized in that In S1, the metal catalyst is a metal element or an intermediate alloy; Preferably, the metal element is Ti, Ce, Sc, Zr, Co, Ni, La or Sm; Preferably, the master alloy is AlNb 10 , AlMo5 or AlV 10 ; Preferably, the inert atmosphere comprises argon; Preferably, the aluminum element is aluminum element particles.

3. The preparation method according to claim 1, characterized in that: In the above S1, the amount of the metal catalyst is 6-10 wt % of the aluminum element.

4. The preparation method according to claim 1, characterized in that: In the above-mentioned S1, the metal catalyst is in a particle state.

5. The preparation method according to claim 1, characterized in that: In S1, the storage pressure during smelting is ≤-0.05MPa; Preferably, during smelting, vacuum is first drawn and then inert gas is introduced; Preferably, the vacuum is evacuated to a vacuum degree of ≤0.003Pa; Preferably, the inert gas is introduced until the pressure in the chamber is -0.05 to -0.1 MPa; Preferably, the aluminum element and the metal catalyst are melted and then further melted under stirring to obtain an aluminum alloy ingot; Preferably, cooling to a solid state after smelting is one smelting, and the number of smeltings is at least 5 times; Preferably, the smelting equipment is a vacuum arc melting furnace.

6. The preparation method according to claim 1, characterized in that: In S1, during the rapid quenching of the melt, vacuum is first drawn and then an inert gas is introduced; Preferably, evacuate to a vacuum degree of ≤0.003Pa; Preferably, an inert gas is introduced until the internal pressure is -0.05 to -0.1 MPa; Preferably, the injection pressure of the inert gas is 0.05 to 0.15 MPa; Preferably, the rotation speed during melt quenching is 1000 to 3000 rpm; Preferably, the heating power during melt quenching is 1 to 2 Kw and maintained for 5 to 20 seconds; Preferably, the equipment for melting and quenching is a high vacuum suspension melting belt furnace.

7. The preparation method according to claim 1, characterized in that: In S2, the molar ratio of aluminum to sodium hydride in the aluminum alloy strip is 1:1; Preferably, the ball milling conditions are: ball-to-material ratio 100-150:1, rotation speed 300-500 rpm / min, time 20-40 h; Preferably, the hydrogen content in the hydrogen-containing reducing atmosphere is ≥ 99.0%; Preferably, the hydrogen pressure of the hydrogen-containing reducing atmosphere is 20 to 60 bar.

8. The sodium aluminum hydride hydrogen storage material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The sodium aluminum hydride hydrogen storage material includes NaAlH4 and Na3AlH6; based on the weight of the sodium aluminum hydride hydrogen storage material, the content of NaAlH4 is above 90wt%.

9. A hydrogen storage material, characterized in that: It comprises the sodium aluminum hydride tetrahydrogen storage material prepared by the preparation method as claimed in any one of claims 1 to 7 or the sodium aluminum hydride tetrahydrogen storage material as claimed in claim 8.

10. A hydrogen storage device, characterized in that: A sodium aluminum hydride tetrahydrogen storage material prepared by the preparation method as described in any one of claims 1 to 7 or a sodium aluminum hydride tetrahydrogen storage material as described in claim 8.